Cases in corporation finance - Andersen, Theodore A. (Holt, Rinehart and Winston, 1962)
Detailed and informed selection of cases illustrating the development of the body of law surrounding corporate finance, including text and explanatory materials. Includes detailed sections analyzing the significance of cases and their points of law.